2021
DOI: 10.1155/2021/6538189
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the Effect of Dapagliflozin on Alcoholic Kidney Injury and Renal Interstitial Fibrosis in Rats Based on TIMP-1/MMP-24 Pathway

Abstract: Objective. To establish a rat model of alcoholic kidney injury and detect the expression of TIMP-1/MMP-24 in the kidneys of rats with alcoholic kidney injury at the molecular pathological level, so as to explore the mechanism of alcohol abuse leading to kidney injury and renal interstitial fibrosis as well as the alleviation of alcohol-induced kidney injury and inhibition of renal interstitial fibrosis by dapagliflozin. Methods. 48 male rats were randomly divided into 4 groups: control group, alcohol group, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A previous case–control study found that alcohol consumption was more frequent in PD cases as compared with a control group, although there was no difference related to the duration of alcohol consumption or types of beverages consumed [ 197 ]. Rat studies have also shown that long-term heavy alcohol consumption increases the expression of fibrotic cytokines such as TIMP-1 and SMAD3, leading to kidney tissue fibrosis [ 182 ]. Additionally, a study that investigated the early effects of alcohol intoxication on liver fibrosis in adolescents reported significantly elevated serum MMP-9 and TIMP-1 concentrations during intoxication [ 183 ].…”
Section: Risk Factors For Pathogenesis Of Peyronie’s Diseasementioning
confidence: 99%
“…A previous case–control study found that alcohol consumption was more frequent in PD cases as compared with a control group, although there was no difference related to the duration of alcohol consumption or types of beverages consumed [ 197 ]. Rat studies have also shown that long-term heavy alcohol consumption increases the expression of fibrotic cytokines such as TIMP-1 and SMAD3, leading to kidney tissue fibrosis [ 182 ]. Additionally, a study that investigated the early effects of alcohol intoxication on liver fibrosis in adolescents reported significantly elevated serum MMP-9 and TIMP-1 concentrations during intoxication [ 183 ].…”
Section: Risk Factors For Pathogenesis Of Peyronie’s Diseasementioning
confidence: 99%
“…This is partly due to the lack of effective drugs. DN as an important cause of CKD, and some drugs treated with diabetes like SGLT2 inhibitors have shown renal protective effects ( Sharma et al, 2017 ; Kelly et al, 2019 ), as a typical drug of SGLT2 inhibitors, dapagliflozin’s renal protective effects on CKD have been demonstrated in patients with and without diabetes ( Kurata and Nangaku, 2022 ) , and it has also displayed antirenal fibrosis activities in animal models induced by unilateral ureter obstruction and alcohol damage ( Wu et al, 2021 ; Xuan et al, 2021 ; Liu et al, 2022 ). In this study, we extended this model to the setting of renal fibrosis induced by a 0.2% adenine diet.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its protective effect in the kidneys of patients with non-diabetic chronic kidney disease, research into the use of dapagliflozin to treat renal fibrosis is underway. Studies have shown that dapagliflozin can reduce renal fibrosis in alcohol-induced kidney injury and unilateral ureteral obstruction (UUO) animal models ( Wu et al, 2021 ; Xuan et al, 2021 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%